2017
DOI: 10.1016/j.commatsci.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Porous graphene and graphenylene nanotubes: Electronic structure and strain effects

Abstract: a b s t r a c tThe unusual and unique mechanical and electronic properties of nanostructured carbon materials make them useful in the construction of nanodevices. We investigate a new class of structures, called porous nanotubes, which are constructed from two recently synthesized two-dimensional materials, namely the porous graphene (PG) and the two-dimensional carbon allotrope known as graphenylene, also known as Biphenylene Carbon (BPC). We investigate this class of quasi-one-dimensional materials using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…43 The difference in results was due to the well-known fact that the PBE functional underestimates the band gap energy; however, considering whether the band gap is direct or indirect, our results were coincident for both chiralities. Also, when compared with a previous theoretical study 40 that utilized the DFTB methodology, the band gap behaviors for PGNTs and GPNTs were also in agreement, and the trend observed in the diameter dependence of the band gap was in reasonable agreement with this work.…”
Section: Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…43 The difference in results was due to the well-known fact that the PBE functional underestimates the band gap energy; however, considering whether the band gap is direct or indirect, our results were coincident for both chiralities. Also, when compared with a previous theoretical study 40 that utilized the DFTB methodology, the band gap behaviors for PGNTs and GPNTs were also in agreement, and the trend observed in the diameter dependence of the band gap was in reasonable agreement with this work.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Fabris et al 40 studied PG nanotubes (PGNTs) and GPNTs for nanotubes with diameters less than 56 Å using the DFTB method, which showed that PGNTs have a wide band gap of ∼3.3 eV, whereas GPNTs have a small band gap of ∼0.7 eV. They also showed that as the diameter of the PGNTs increases, the band gap decreases, whereas for GPNTs, the band gap increases with the PGNT diameter; these results are in agreement with those presented by Koch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows a large band gap with an energy of 3.3 eV. Meanwhile, a nanotube graphenylene has a band gap energy of 0.7 eV [19] .…”
Section: Introductionmentioning
confidence: 95%
“…By DFT calculations, they showed that graphenylene nanotubes with 'zigzag' edges are semiconductors with a small bandgap values, while narrow 'armchair' tubes exhibit metallic properties and become semiconducting for increased diameters. In [14], computational results on electronic structure and strain effects of porous graphene and graphenylene nanotubes are presented and analyzed. Fabris et al [14] have found that axial strain applied to graphenylene nanotubes can lead to substantial increase of the bandgap (up to 100% in some cases).…”
Section: Introductionmentioning
confidence: 99%